2009
DOI: 10.1002/eji.200838804
|View full text |Cite
|
Sign up to set email alerts
|

Induction of adaptive immunity by flagellin does not require robust activation of innate immunity

Abstract: The ability of TLR agonists to promote adaptive immune responses is attributed to their ability to robustly activate innate immunity. However, it has been observed that, for adjuvants in actual use in research and vaccination, TLR signaling is dispensable for generating humoral immunity. Here, we examined the role of TLR5 and MyD88 in promoting innate and humoral immunity to flagellin using a prime/boost immunization regimen. We observed that eliminating TLR5 greatly reduced flagellin-induced cytokine producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 67 publications
6
74
2
2
Order By: Relevance
“…However, since conjugate vaccines are extracellular antigens, activation of NLRC4/Ipaf may be negligible (41). Work in transgenic mice suggests that the immunogenicity and adjuvanticity of flagellin may be TLR independent (54). In these experiments, comparable antiflagellin antibody levels and a measurable adjuvant boost against coadministered ovalbumin were seen between TLR5-deficient and wild-type mice.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, since conjugate vaccines are extracellular antigens, activation of NLRC4/Ipaf may be negligible (41). Work in transgenic mice suggests that the immunogenicity and adjuvanticity of flagellin may be TLR independent (54). In these experiments, comparable antiflagellin antibody levels and a measurable adjuvant boost against coadministered ovalbumin were seen between TLR5-deficient and wild-type mice.…”
Section: Discussionmentioning
confidence: 65%
“…In these experiments, comparable antiflagellin antibody levels and a measurable adjuvant boost against coadministered ovalbumin were seen between TLR5-deficient and wild-type mice. In the absence of TLR5 signaling, high antiflagellin IgG levels may be due, in part, to partial activation of NLRC4/Ipaf (66) or highly efficient cross-linking of B-cell receptors due to the polymeric nature of the antigen or possibly through efficient antigen processing and presentation on major histocompatibility complex (MHC) molecules of flagellin epitopes (2,3,8,54). Furthermore, as anti-LPS antibody levels were similar between flagellin-and CRM 197 -based conjugates, in contrast to the powerful adjuvant boost that flagellin bestows on protein antigens, the comparative adjuvanticity toward polysaccharide antigens may be modest.…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune agonist FliC activates different pattern recognition receptors (24)(25)(26). In our study, we investigated the activation of TLR-4, TLR-5, and MyD88 by immunizing wild-type (WT), as well as TLR-4, TLR-5, and MyD88 KO mice with His 6 -FliC-VK210.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of TLR5 had a more profound effect on IgA than IgG responses. Sustained IgG titers after flagellin in TLR5 2/2 mice has been described, where NLRC4 can provide some compensation for its loss (32,42). The near absolute loss of IgA to sFliC in TLR5 2/2 mice suggests that TLR5 may have a nonredundant role in the generation of IgA in this response.…”
Section: Discussionmentioning
confidence: 97%
“…Flagellin is an important immunodominant and immunomodulatory protein with autoadjuvant properties, with a clear, although not exclusive (32), dependence on TLR5 for these activities (33). Previously, we showed that the immune response to flagellin within the same SLT can show significant plasticity (21).…”
Section: Discussionmentioning
confidence: 99%